High energy trauma of the upper extremity with traction injury of the brachial plexus - Gordana Georgieva; Boro Dzonov; Gjorgje Dzokic; Bisera Nikolovska; Tomislav Jovanoski; Blagoja Srbov; Sofija Pejkova (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2021)
As a severe peripheral nerve injury, brachial plexus lesion can cause limitation in every- day home and workplace activities. Hereby, we present a patient with high-energy trauma of the upper extremity. The examination showed motor weakness of the upper extremity and no flexion and extension in the wrist and fingers with sensibility impairment. The examination and mechanism of injury indicated traction lesion of the brachial plexus. MRI showed postganglionic stretch injury. Treatment of choice was physical therapy. To evaluate the function of the upper extremity after the injury, we used the DASH score. Four months post injury, the patient has flexion and extension in the wrist and fingers. The mechanism of injury and the magnitude of forces that caused the injury can guide as to the extent of the brachial plexus lesion. Analyzing the acquired information, a plan for initial treatment can be established. On point treatment can increase patient’s quality of life with better outcome.
Keywords: brachial plexus injuries